2010
DOI: 10.1074/jbc.m110.141168
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Inhibits Cytoskeleton Reorganization and Cell Motility by Suppressing RhoA Expression and Activity

Abstract: The mammalian target of rapamycin (mTOR) functions in cells at least as two complexes, mTORC1 and mTORC2. Intensive studies have focused on the roles of mTOR in the regulation of cell proliferation, growth, and survival. Recently we found that rapamycin inhibits type I insulin-like growth factor (IGF-1)-stimulated lamellipodia formation and cell motility, indicating involvement of mTOR in regulating cell motility. This study was set to further elucidate the underlying mechanism. Here we show that rapamycin inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
106
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 52 publications
10
106
2
1
Order By: Relevance
“…As shown in 4B, PI-103, and rapamycin had little effect on the protein expression of these GTPases, whereas PP-242 slightly inhibited protein expression of RhoA and Rac1. The inconsistency between our results and previous report (19) might reflect different cell types used and time of treatment in the studies. We next examined the active form of RhoA, Rac, and Cdc42 upon inhibition of PI3K and mTOR signaling using a pulldown assay that specifically recognizes the active GTP-bound forms.…”
Section: Compounds Targeting Pi3k/mtor Pathway Prevented F-actin Reorcontrasting
confidence: 56%
See 2 more Smart Citations
“…As shown in 4B, PI-103, and rapamycin had little effect on the protein expression of these GTPases, whereas PP-242 slightly inhibited protein expression of RhoA and Rac1. The inconsistency between our results and previous report (19) might reflect different cell types used and time of treatment in the studies. We next examined the active form of RhoA, Rac, and Cdc42 upon inhibition of PI3K and mTOR signaling using a pulldown assay that specifically recognizes the active GTP-bound forms.…”
Section: Compounds Targeting Pi3k/mtor Pathway Prevented F-actin Reorcontrasting
confidence: 56%
“…The CXCL12/CXCR4 axis and its downstream signaling could be therapeutic targets for preventing metastasis of gastric cancer. Moreover, it has been reported that both mTORC1 and mTORC2 play critical roles in the regulation of tumor cell motility and cancer metastasis (12,19). We found that the CXCL12/CXCR4 axis was able to activate the PI3K/mTOR pathway and stimulate cell migration in human MKN-45 gastric cancer cells.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Our results presented here strongly suggest that the defect in mTORC1 signaling resulting from dysregulation of the MID1/PP2A axis is one of the avenues leading to OS pathogenesis. Of note, malformations occurring in OS patients have been attributed to defective migration patterns of neural crest cells needed to mediate ventral midline tissue formation in a very specific time window during development (1), and mTORC1 signaling not only is responsible for cytoskeleton dynamics and intracellular transport-both processes that significantly influence the migration potential of cells-but also has a direct regulatory function in migrating cells (52,53). Dysfunctional mTORC1 signaling in OS patients with MID1 mutations is therefore likely to significantly contribute to the OS phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…2008) and promote RhoA expression and activity (Liu et al. 2010). RhoA activity is also modulated by Abl family kinases (Bradley and Koleske 2009).…”
Section: Introductionmentioning
confidence: 99%